2002
DOI: 10.3386/w9393
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Exchange Rate Models of the Nineties: Are Any Fit to Survive?

Abstract: Previous assessments of nominal exchange rate determination have focused upon a narrow set of models typically of the 1970's vintage. The canonical papers in this literature are by Rogoff (1983, 1988), who examined monetary and portfolio balance models. Succeeding works by Mark (1995) and Chinn and Meese (1995) focused on similar models. In this paper we re-assess exchange rate prediction using a wider set of models that have been proposed in the last decade: interest rate parity, productivity based models, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
209
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(219 citation statements)
references
References 16 publications
(19 reference statements)
7
209
1
2
Order By: Relevance
“…Their result that these models 6 cannot out-perform a naive random-walk specification has proven robust. For many years researchers have found it difficult to reject the hypothesis that major country exchange rates follow a random walk under floating exchange rate regimes; see, for example, Meese and Rogoff (1983), Rogoff (1996) and, Cheung et al, (2005). An implication of this finding is that the prospect of having a commonly agreed framework to assess exchange rate misalignment is pretty unpromising.…”
Section: Undervalued or Overvaluedmentioning
confidence: 87%
“…Their result that these models 6 cannot out-perform a naive random-walk specification has proven robust. For many years researchers have found it difficult to reject the hypothesis that major country exchange rates follow a random walk under floating exchange rate regimes; see, for example, Meese and Rogoff (1983), Rogoff (1996) and, Cheung et al, (2005). An implication of this finding is that the prospect of having a commonly agreed framework to assess exchange rate misalignment is pretty unpromising.…”
Section: Undervalued or Overvaluedmentioning
confidence: 87%
“…As is now widely accepted, it is difficult to obtain a conclusive set of results from conventional tests of exchange rate models at this horizon (Cheung, Chinn, and Pascual, 2005;Engel and West, 2005) and so in this paper we propose another route.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, market participants do not only use fundamentals but also non-fundamentals as information in their decision making (Menkhoff and Taylor, 2007). Each of these sources of complexity may explain why conventional tests of exchange rate models in the spirit of Meese and Rogoff (1983) -regressing exchange rate changes on changes in fundamentals -fail (Cheung, Chinn, and Pascual, 2005): the reason is not necessarily the above mentioned "disconnect" but possibly the use of a "false" model, i.e. a model that cannot account well enough for existing complex 1 relations.…”
Section: Introductionmentioning
confidence: 99%
“…First, Faust et al (2003) have shown that these long horizon results are specific to the particular time period examined, particularly in the case of Mark's study. 10 Second, examining a slightly different set of models, and taking into account the possibility of no-cointegration, Cheung, Chinn and Garcia Pascual (2005) find only very limited evidence of improved forecasting ability at long horizons, relative to shorter horizons. Specifically, they examine a more recent set of models developed over the last two decade --interest rate parity, 11 productivity based models, and "behavioral equilibrium exchange rate" models.…”
Section: Empirical Evidencementioning
confidence: 99%